1988
DOI: 10.1007/bf03350185
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and pancreatic islet function I. Time course for changes in insulin secretion and content during vitamin D deprivation and repletion

Abstract: After weaning, rats were given free access to a control or vitamin D-deprived diet for 2 to 5 weeks. In the vitamin D deficient rats, plasma concentrations of 25-(OH)D3, 1,25-(OH)2D3,24,25-(OH)2D3 calcium, glucose and insulin were all decreased. After an overnight fast, the plasma insulin concentration was also decreased even when the plasma glucose concentration was not significantly affected. The food intake and body growth was also impaired in vitamin D-deficient rats. Administration of vitamin D3 in oil fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Rats were housed in a dark room and had free access to food and water. As previously described (Labriji-Mestaghanmi et al 1988, Bourlon et al 1996 such a 4-week vitamin D 3 deficiency induced rachitism, with a smaller body weight ( 0·3), hypoglycaemia ( 0·7), and relative hypocalcaemia ( 0·8). Pancreatic islets were isolated by collagenase digestion (Lacy & Kostianovsky 1967).…”
Section: Animals and Isolation Of Islets Of Langerhansmentioning
confidence: 62%
See 1 more Smart Citation
“…Rats were housed in a dark room and had free access to food and water. As previously described (Labriji-Mestaghanmi et al 1988, Bourlon et al 1996 such a 4-week vitamin D 3 deficiency induced rachitism, with a smaller body weight ( 0·3), hypoglycaemia ( 0·7), and relative hypocalcaemia ( 0·8). Pancreatic islets were isolated by collagenase digestion (Lacy & Kostianovsky 1967).…”
Section: Animals and Isolation Of Islets Of Langerhansmentioning
confidence: 62%
“…The rat endocrine pancreas is one of these non-classical target tissues presenting 1,25(OH) 2 D 3 receptors ( Johnson et al 1994), even in vitamin D 3 -deficient rats (Clark et al 1980, Ishida & Norman 1988. Several studies have demonstrated a regulatory role for 1,25(OH) 2 D 3 in improving the insulin release that is dramatically reduced by vitamin D 3 deficiency (Norman et al 1980, Clark et al 1981, Chertow et al 1983, Labriji-Mestaghanmi et al 1988. 1,25(OH) 2 D 3 acts, at least in part, as a steroid in numerous tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Kadowaki and Norman [17] in isolated perfused rat pancreas and Cade and Norman [21] in rats have demonstrated that vitamin D deficiency reduces only the peak of monophasic insulin response induced by boluses o f tolbutamide [17] or glucose [21], It is still unclear whether the effect of vitamin D on insulin secretion is due to a direct action on pancreatic [1-cell or to elevation o f serum calcium levels. Some studies in animals [17][18][19] have excluded hypocalcemia as a possible cause of inhibition of insulin secretion in the vitamin Ddeficient state and Mak [27] and Quesada et al [25] have in M H patients found an increase in glucose-induced insulin secretion after calcitriol administration despite the lack of changes in serum calcium levels. On the contrary, Tanaka et al [34] in in vivo and perfusion experiments have found that calcium, not la,25(HO)2-vitamin D 3, is essential for the reversal o f impaired insulin release in vitamin D-deficient rats.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D and metabolic diseases (33)(34)(35)(36)(37) and IR (7,33,34) , the primary underlying defects characterising T2D. It has also been reported that direct action of 1,25-dihydroxyvitamin D, may lead to increased expression of insulin receptor and enhanced insulin responsiveness for GLUT (38,39) .…”
Section: Commentmentioning
confidence: 99%